Unclassified bleeding disorders: outcome of haemostatic challenges following tranexamic acid and/or desmopressin. (30th September 2015) - Obaji, S.; Alikhan, R.; Rayment, R.; Carter, P.; Macartney, N.; Collins, P.
Abstract : Introduction: In a minority of patients with a significant bleeding history no cause is found despite extensive testing and we diagnose such cases as unclassified bleeding disorders (UBD). UBDs may have diverse underlying causes and currently no standard management strategy exists in the event of a haemorrhage or to cover surgery. Aim: To document the clinical characteristics and response to treatment of UBDs. Methods: We performed a retrospective chart review of all patients with UBDs who had an invasive procedure at our centre between 1998 and 2014. Results: The commonest symptoms were menorrhagia (89%) and bleeding at the time of surgery (88%) or dental extraction (85%). A total of 33 patients underwent 78 minor and major haemostatic challenges. Haemostatic cover was provided in 28 procedures with tranexamic acid alone, two with desmopressin and 45 with both agents in combination. A successful haemostatic outcome was observed in 70/78 (90%) cases. No patient required additional surgical intervention to achieve haemostasis, but one patient required a platelet transfusion to control postoperative bleeding. Conclusions: This is the first study to report on the investigation and treatment of UBD. Future studies are needed to further our understanding of the bleeding phenotype and identify any underlying causes.